Produção e utilização de energia no contexto do agronegócio tocantinense em uma perspectiva CTS para ensino médio técnico. - Pereira, Nádia Vilela (2020)
This research investigated the results of the introduction of interventions pedagogies supported by CTS (Science, Technology and Society) education, using as a theme the production and use of “Energy”, developed in the discipline of Physics for students of the third year of Administration and Agribusiness from High School Integrated to Technical Education at IFTO (Instituto Federal do Tocantins) - Campus Palmas. Activities related to the students' daily activities were proposed, which involved the specific content of this curricular component. In the intervention activities, the contents were approached, emphasizing the production and consumption of energy, seeking to articulate socioenvironmental issues within the context of agribusiness in the state of Tocantins. For the research, we opted for a qualitative approach and the instruments used in the data collection were two questionnaires, one with open questions and another with closed questions, applied in the pre and post intervention activities corresponding to the beginning and end of the school year, in addition to observations made in the classroom during the same period. The results of the interventions were verified through Content Analysis and by comparing two questionnaires, with the aim of identifying changes in students' perception regarding important aspects and objectives of CTS education. The results pointed to the students' awareness of their responsibility and professional citizenship, as well as showing a more humanized Physics, changing the usual conception that it is a “hard and exact” Science. The developed proposal can contemplate other themes and involve other disciplines, in an interdisciplinary or multidisciplinary way, aiming to provide students with training capable of broadening their understanding of scientific and technological knowledge, making it possible to unveil the mechanisms by which this knowledge influences and transforms society, favoring the development of values and attitudes, in addition to critical and reflective thinking.